Influence of cyclodextrin on the solubility of a classically prepared 2-vinylcyclopropane macromonomer in aqueous solution - Ritter, Helmut; Cheng, Jia; Tabatabai, Monir (Beilstein Journal of Organic Chemistry, 2012)
A macromonomer 5 consisting of a polymerizable vinylcyclopropane end group and a poly(N-isopropylacrylamide) (poly(NiPAAm)) chain was obtained from amidation of 1-ethoxycarbonyl-2-vinylcyclopropane-1-carboxylic acid (4) with an amino-terminated poly(NiPAAm) 3 as an example. This macromonomer 5 showed an LCST effect after complexation of the vinyl end group with ß-cyclodextrin in water. Via radical ring-opening copolymerization of 5 and NiPAAm a graft copolymer 8 with a clouding point of 32 °C was synthesized. The branched unsaturated polymer was treated with ozone to cleave the double bonds of the main chain.
Keywords: branched poly(NiPAAm); cloud point; cyclodextrins; graft copolymer; macromonomer; ring-opening free radical polymerization; 2-vinylcyclopropane